2014
DOI: 10.1186/1471-2474-15-315
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent whole-body vibration attenuates a reduction in the number of the capillaries in unloaded rat skeletal muscle

Abstract: BackgroundWhole-body vibration has been suggested for the prevention of muscle mass loss and muscle wasting as an attractive measure for disuse atrophy. This study examined the effects of daily intermittent whole-body vibration and weight bearing during hindlimb suspension on capillary number and muscle atrophy in rat skeletal muscles.MethodsSixty male Wistar rats were randomly divided into four groups: control (CONT), hindlimb suspension (HS), HS + weight bearing (WB), and HS + whole-body vibration (VIB) (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 45 publications
(59 reference statements)
2
18
1
Order By: Relevance
“…ANG is also a potent stimulator of angiogenesis, specifically up-regulating the production of proteases that degrade laminin and fibronectin, allowing endothelial cells to migrate and form new vessels (45,46). This information suggests that lack of ANG production by pericytes during IM may contribute to suppression of protein synthesis and atrophy, as well as reductions to capillary number (C/F ratio) or capillary density (capillary per square millimeter tissue) following disuse (47)(48)(49)(50). In addition to the change in Ang gene expression, the increases in Atf4 and p53 in NG2 + Lin 2 pericytes post-IM were also striking.…”
Section: Discussionmentioning
confidence: 99%
“…ANG is also a potent stimulator of angiogenesis, specifically up-regulating the production of proteases that degrade laminin and fibronectin, allowing endothelial cells to migrate and form new vessels (45,46). This information suggests that lack of ANG production by pericytes during IM may contribute to suppression of protein synthesis and atrophy, as well as reductions to capillary number (C/F ratio) or capillary density (capillary per square millimeter tissue) following disuse (47)(48)(49)(50). In addition to the change in Ang gene expression, the increases in Atf4 and p53 in NG2 + Lin 2 pericytes post-IM were also striking.…”
Section: Discussionmentioning
confidence: 99%
“…One study reports no change in VEGF expression during HU-induced capillary regression, but significant reductions in the VEGF receptors, and in angiopoietin (Ang)-1 & Ang-2 signaling through its Tie-2 receptor [106]. Two other studies report decreased VEGF expression, with no significant change in TSP-1 protein expression, in conjunction with HU [52,53]. However, one of these studies report a 62-fold increase in the TSP-1 receptor CD-36 [53], suggesting that activation of TSP-1 signaling pathway was likely to occur even if TSP-1 itself was not elevated.…”
Section: Capillary Regression Correlates Better To Changes In Tsp-1 Tmentioning
confidence: 99%
“…Two other studies report decreased VEGF expression, with no significant change in TSP‐1 protein expression, in conjunction with HU . However, one of these studies report a 62‐fold increase in the TSP‐1 receptor CD‐36 , suggesting that activation of TSP‐1 signaling pathway was likely to occur even if TSP‐1 itself was not elevated. The CD36 pathway is important in this context, becuase it is believed to be the primary receptor responsible for TSP‐1 anti‐angiogenic effects .…”
Section: Introductionmentioning
confidence: 99%
“…The potential of a vibratory stimulus (whether applied locally or to the whole body using a platform) to increase muscle mass and performance in healthy subjects has been previously discussed [53]. Previous animal studies applying isolated vibration have reported benefits at the muscle level [21,37,74]. Yet, the potential benefits of vibration per se (i.e., independently of RET) on human muscle mass remain to be clearly shown.…”
Section: Vibrationmentioning
confidence: 99%